Synergistic effect of nitrogen-doped carbon-nanotube-supported Cu–Fe catalyst for the synthesis of higher alcohols from syngas. (15th December 2017) - Shi, Xinping; Yu, Haibing; Gao, Shan; Li, Xiaoyun; Fang, Huihuang; Li, Rongjun; Li, Yuyang; Zhang, Lijie; Liang, Xuelian; Yuan, Youzhu
Graphical abstract: Highlights: Cu−Fe/N-CNT catalysts with different nitrogen contents are synthesized. Cu−Fe/N-CNT catalysts show good performance in the synthesis of higher alcohols from syngas. An improved CO conversion and excellent selectivity to higher alcohols were obtained. The electron donation and surface basicity of N-CNT account for the promotional effects. Abstract: Heteroatom doping is an attractive approach for improving the properties of carbon materials for various applications. In this study, a series of nitrogen-doped (N-doped) carbon-nanotube-supported Cu–Fe ( x Cu n –Fe m / y N-CNT) catalysts were prepared for CO hydrogenation to higher alcohols. The structural and textural properties of N-doped catalysts were characterized by X-ray diffraction, transmission electron microscopy, hydrogen temperature-programmed reduction, and CO2 temperature-programmed desorption. The results revealed that doping N into CNT supports improved the Cu–Fe dispersion, strengthened the interaction of Cu and Fe species with N-CNT, and introduced many surface-basicity sites. Thus, an improved CO conversion and excellent selectivity to higher alcohols [ S (C2+ –OH)] were obtained. Furthermore, the selectivity to alcohols [ S (ROH)] and S (C2+ –OH)/ S (MeOH) over the optimized 15Cu1 –Fe1 /1.3N-CNT catalyst reached 27.2% and 2.2, while the corresponding values were 20.2% and 0.4, respectively, over the catalyst without N doping under identical reaction conditions. The present results on N-CNT supported Cu–Fe catalyst will provide further understanding on the catalyst design for the transformation of syngas to higher alcohols.